Work skills and Training as an Efforts to Improve Production - Agus Supandi; Arief Nugroho Wibowo (International Journal of Education, Information Technology, and Others, 2020)
Training and skills are important factors that must be possessed by every employee. This research aims to describe the role of skills and training to increase production in the CV Berkah Saintek relatively low employee performance supported by research results. This research is a descriptive qualitative research, the subject of this study is the employee of CV Blessing Sainteks Data collection is done by observation, interview, and survey techniques. The validity of the data is done by triangulation of techniques and sources. Data analysis techniques using qualitative descriptive analysis techniques. The results showed that the training and skills carried out by CV Berkah Saintek were good enough, but needed improvement, and the addition of material. Training and skills can improve production results, because employees get enough training, if there is additional production.